Compatibility and efficiency of preservatives in emulsive cosmetics containing high surfactant content - Priscila de Oliveira Schmitt; Ana Flávia Fischer; Ruth Meri Lucinda da Silva; Alexandre Bella Cruz (Universidade de São Paulo, 2022)
Abstract The objective of this study was to determine the influence of nonionic surfactants on the effectiveness of preservatives used in emulsions containing high surfactant content. Mixtures of different concentrations were prepared between polyethoxylated (40) hydrogenated castor oil (PHCO) and polyoxyethylene sorbitan monooleate (PSO), with methylparaben, phenoxyethanol, methylparaben, ethylparaben, propylparaben, and isobutylparaben (PMEPBI) blend, phenoxyethanol and benzoic acid (BP) blend, and phenoxyethanol and caprylyl glycol (PC) blend. Subsequently, the compatibility of the formulation ingredients and the effectiveness of the preservatives were evaluated by the challenge test. It was found that PHCO and PSO inactivated the antimicrobial action of methylparaben and PMEPBI. Paraben-free preservatives BP and PC had less influence on surfactants than systems containing parabens. When incorporated into microemulsions and nanoemulsions containing 40% and 20% surfactants, methylparaben and BP 0.2% and 0.5% were only effective against Aspergillus niger. The PMEPBI 0.2% was effective as a preservative in nanoemulsified formulations against A. niger, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. The results demonstrate that the efficacy of the preservative system in formulations containing nonionic surfactant excipients depends on the type of excipient, the components of the formulation, the preservative systems composition, the excipient to preservative ratio, and the availability in the formulation.